KARAKTERISTIK RAVELLING RESISTANCE, MOISTURE SENSITIVITY, DAN WORKABILITY LASTON AC-WC DENGAN BAHAN TAMBAH POLIVINIL KLORIDA (PVC) - Khanza, Ayu Kamila; Michael, Michael; Helmi Maulana Ramadan (Nusantara Hasana Journal, 2025)
This study aims to evaluate the effect of 4% waste addition on the characteristics of the asphalt concrete wearing course (AC-WC) mixture, including raveling resistance, moisture sensitivity, and workability. The study used a dry mix method with 60/70 penetration asphalt, according to the 2018 General Specification of Bina Marga Division 6. The results showed an increase in mixture performance in the Tensile Strength Ratio (TSR) value increasing from 95.10% to 99.86%, and Cantabro Loss decreasing from 5.16% to 3.47%. Workability testing showed that the Void in Mix (VIM) value in the PVC mixture was higher than the control in each impact variation (5–100), indicating that the control was easier to compact. VIM increased in the 5th impact from 14.530% to 15.316% and in the 100th from 3.409% to 4.617%, indicating a slight decrease in compaction ease. This condition occurs because PVC has a relatively high melting point and a rigid molecular structure, so during the compaction process, the PVC particles do not fully soften with the flow of asphalt, which causes more air voids to remain. Overall, the addition of PVC has been shown to effectively increase wear resistance and moisture resistance, with a slight increase in compaction ease.